Pengaruh Protein Hewani Terhadap Penurunan Angka Stunting Pada Anak Di Kampung Tengah - Nursiani Lubis; Iqbal Parija; Dzaki Mohammad Haspian; Muhammad Nadhel Akbar; Muhammad Zaky Al Hafiz; Putri Harmadani; Siti Nurjannah; Nilam Sari; Suci Andini; Ummi Hasanah; Lora Septiana (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Stunting is a problem that occurs in babies and toddlers which is characterized by the toddler's height and weight not being in accordance with general standards. Stunting can be caused by inappropriate parenting patterns, inadequate nutrition, and economic factors. The purpose of writing this article is to determine the role of animal protein in reducing stunting rates in children in Central Villages, which is done through providing additional food containing animal protein. The method used in making this article is the literature review method, where we look at several article sources that are related to the topic we are discussing, then we carry out this additional feeding activity by considering the use of animal protein in providing nutrients that are useful for growth and development. child flower. The results of this research are that the animal protein content in eggs, both chicken eggs and quail eggs, greatly influences the adequacy of animal protein in children.